A Systematic Review of Magnetic Resonance Imaging for the Diagnosis of Stroke - Kalsoom Nawab, Anwar Ul Haq, Mehmood Akhtar Khattak, Hina Gul, Naheed Khan, Irsa Shoaib (Pakistan Journal of Medical & Health Sciences, 2023)
Background: With the advancement of magnetic resonance imaging (MRI), a non-invasive imaging technique, ischemic and hemorrhagic stroke diagnostic accuracy has increased significantly. The intricate resolution of MRI enables better visualisation of the structure of the brain and vulnerable regions to ischemia. As a result, the detection of hypoperfused areas is now more accurate. Additionally, MRI makes it possible to see hematomas in the brain, revealing hemorrhagic strokes brought on by burst arteries. MRI has become an essential tool in the fight against strokes because to its crucial role in evaluating damage caused by strokes. Purpose: The purpose of this article is to examine the advantages and disadvantages of utilising MRI scans to identify strokes. The use of MRI technology to identify brain injury and differentiate between strokes caused by blood flow and haemorrhage will be highlighted. When it comes to stroke therapy and prognosis, MRI might potentially affect the advice given by doctors. Methods: The Department of Radiology at KTH Hospital Peshawar thoroughly investigated the possibility of MRI for stroke diagnosis between March 2016 and March 2017. We searched the PubMed and EMBASE archives for papers about the use of MRI in stroke patient investigations in order to assemble the most information possible. We only chose studies that have a main concentration on MRI imaging and stroke patients. Results: Twenty-nine research publications examined the efficiency of MRI with an emphasis on stroke diagnosis. Twenty-four of them examined ischemic stroke diagnosis, while the remaining five concentrated on hemorrhagic stroke diagnosis. Findings showed that MRI was very accurate, with a sensitivity and specificity of up to 97% for ischemic stroke detection. MRI shown success in the diagnosis of hemorrhagic stroke, with a sensitivity and specificity of up to [100%]. Conclusions: MRI is a crucial tool for the diagnosis and treatment of stroke. Because of the great accuracy and sensitivity of this imaging method, both ischemic and hemorrhagic strokes may be identified. It also carefully evaluates the effects of a stroke on the brain. The early and successful diagnosis and treatment of stroke depend heavily on the use of MRI. Keywords: diagnosis, ischemic stroke, hemorrhagic stroke, and magnetic resonance imaging